Whispering void - Eneroth, Joakim 1969-; Gustafsson, Paula (Arvinius+Orfeus, 2017)
In 'Whispering Void', artist Joakim Eneroth explores the nature of the mind from a Western psychological perspective combined with contemporary neuroscience. It is a continued examination of the theme, which was investigated in his previous art project 'Short Stories of the Transparent Mind' from an Eastern philosophical point of view. In 'Whispering Void', Eneroth reveals the deeper subconscious layers of experience, the dance of notions and perceptions in the fluctuating mind. The questions often revolve around how to distinguish the mental projections of the mind from reality itself
Keywords: Eneroth, Joakim -- 1969-; Fotografie; Bildband